2006
DOI: 10.1111/j.1365-2419.2005.00390.x
|View full text |Cite
|
Sign up to set email alerts
|

Annual cycle of clupeiform larvae around Gran Canaria Island, Canary Islands

Abstract: The distribution and abundance of fish larvae was studied along the eastern and southern shelf of Gran Canaria Island (Canary Islands) from July 2000 to June 2001. Oblique bongo hauls were carried out fortnightly during the daytime, coinciding with days of full and new moon. During February, the area was sampled every 2–5 days. About 17.3% of the ichthyoplanktonic community was composed of clupeiform larvae: 92.9% of these larvae were Sardinella aurita, whereas 4.7% and 2.4% were respectively Engraulis encrasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 31 publications
1
25
0
Order By: Relevance
“…Furthermore, most of these studies consisted in short-time surveys and their sampling stations were either located in the oceanic region or near the coastal upwelling. Only Bécognée et al (2006) carried out an annual study in shallow waters off Gran Canaria, but their study only focused on clupeoid and scombrid larvae. Therefore, the main goal of this work was to analyze the temporal and horizontal variations of the ichthyoplankton distribution and composition off Gran Canaria.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, most of these studies consisted in short-time surveys and their sampling stations were either located in the oceanic region or near the coastal upwelling. Only Bécognée et al (2006) carried out an annual study in shallow waters off Gran Canaria, but their study only focused on clupeoid and scombrid larvae. Therefore, the main goal of this work was to analyze the temporal and horizontal variations of the ichthyoplankton distribution and composition off Gran Canaria.…”
Section: Introductionmentioning
confidence: 99%
“…Satellite images (Hernández-Guerra et al 1993;Arístegui et al 1997;Barton et al 2004) have shown that eddies detached from the central and eastern islands of the Archipelago, occasionally interact with the offshore boundary of the filaments, entraining upwelled water and extending their transport much further westward. Several authors have observed that fish larvae displaced by the filament system can be transported towards the innermost islands (Rodríguez et al 2004) to reach the coasts of Gran Canaria Island (Bécognée et al 2006;Moyano et al 2009). Therefore, if the larvae are able to avoid predation, the filaments could maintain a unidirectional gene flow between the invertebrate populations of the African coast and Canary Islands, playing a significant role in dispersal and connectivity.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the advection pattern depicted by the mud shrimp larvae has almost exactly the same horizontal distribution as that observed for Sardina pilchardus larvae by Rodríguez et al (1999) when they studied the ichthyoplankton on this same cruise. The larvae of S. pilchardus are considered a good tracer of the movement of African upwelled waters by filaments in this region (Bécognée et al 2006;Moyano et al 2009). Thus, the correlation between two larval patterns also supports the association with the filament.…”
Section: Discussionmentioning
confidence: 99%
“…UF are characterized by elevated concentrations of phytoplankton (Barton et al 1998, Baltar et al 2009) and mesozooplankton (Rodríguez et al 2004, Hernández-León et al 2002a, Yebra et al 2004) that can enable higher survival rates of decapod larvae during their transport within the filaments (Anger 2001). Recently, intensive monitoring programmes conducted on the island shelf of GC have confirmed the relationship between UF and the presence of African larvae in the planktonic insular community (Bécognée et al 2006). Specifically, these works observed that Sardina pilchardus and Engraulis encrasicolus larvae, considered good tracers for UF in the C-ACTZ area (Rodríguez et al 1999(Rodríguez et al , 2004, were collected only during specific short periods, always coinciding with the arrival of filaments to the islands.…”
Section: The African Continent As a Larval Sourcementioning
confidence: 99%
“…In the case of fish larvae, Rodríguez et al (1999) proposed the filament-eddy combination as a favourable retention mechanism for African neritic species, but it can also produce significant larval advection towards the ocean domain (Rodríguez et al 2004, Bécognée et al 2009). Occasionally, these African larvae can reach the vicinity of the Canary Islands (Bécognée et al 2006, Brochier et al 2008.…”
Section: Introductionmentioning
confidence: 99%